Immunosuppression mediated by myeloid-derived suppressor cells (MDSCs) during tumour progression - Groth, Christopher; Bitsch, Rebekka; Fleming, Viktor; Altevogt, Peter; Utikal, Jochen; Umansky, Viktor; Hu, Xiaoying (British journal of cancer, 2018)
Under steady-state conditions, bone marrow-derived immature myeloid cells (IMC) differentiate into granulocytes, macrophages and dendritic cells (DCs). This differentiation is impaired under chronic inflammatory conditions, which are typical for tumour progression, leading to the accumulation of IMCs. These cells are capable of inducing strong immunosuppressive effects through the expression of various cytokines and immune regulatory molecules, inhibition of lymphocyte homing, stimulation of other immunosuppressive cells, depletion of metabolites critical for T cell functions, expression of ectoenzymes regulating adenosine metabolism, and the production of reactive species. IMCs are therefore designated as myeloid-derived suppressor cells (MDSCs), and have been shown to accumulate in tumour-bearing mice and cancer patients. MDSCs are considered to be a strong contributor to the immunosuppressive tumour microenvironment and thus an obstacle for many cancer immunotherapies. Consequently, numerous studies are focused on the characterisation of MDSC origin and their relationship to other myeloid cell populations, their immunosuppressive capacity, and possible ways to inhibit MDSC function with different approaches being evaluated in clinical trials. This review analyses the current state of knowledge on the origin and function of MDSCs in cancer, with a special emphasis on the immunosuppressive pathways pursued by MDSCs to inhibit T cell functions, resulting in tumour progression. In addition, we describe therapeutic strategies and clinical benefits of MDSC targeting in cancer.